2020
DOI: 10.1155/2020/5125243
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effects of 1% Atropine on the Anterior Segment

Abstract: Purpose. To investigate the influences of atropine on changes in anterior segment geometry, as measured by ultrasound biomicroscopy in children. Methods. A prospective observational study was performed. Anterior segment parameters were obtained by UBM before and after the instillation of 1% atropine. Univariate linear regression was performed to identify the variables contributing to the changes in the trabecular meshwork-iris angle (TIA). Results. The study included 21 boys and 37 girls with a mean age of 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…These processes, together with retrograde ow through the trabecular meshwork in the setting of hypotony, cause the pressure in the anterior chamber to rise above that in the posterior chamber, resulting in posterior bowing of the iris [23]. Third, Zhou et al reported that use of atropine could increase the ACA measured by Pentacam, which is similar to our study [24]. Moreover, Fernández-Vigo et al [25] showed that Pentacam tends to overestimate the measurements of narrow angles and underestimate that of open angles in comparison with OCT measurements.…”
Section: Discussionsupporting
confidence: 89%
“…These processes, together with retrograde ow through the trabecular meshwork in the setting of hypotony, cause the pressure in the anterior chamber to rise above that in the posterior chamber, resulting in posterior bowing of the iris [23]. Third, Zhou et al reported that use of atropine could increase the ACA measured by Pentacam, which is similar to our study [24]. Moreover, Fernández-Vigo et al [25] showed that Pentacam tends to overestimate the measurements of narrow angles and underestimate that of open angles in comparison with OCT measurements.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have demonstrated that atropine drugs used for treating myopia effectively relieve tension in ciliary muscles, resulting in complete muscle relaxation, thereby eliminating the problem of pseudomyopia due to eye fatigue [13].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating proportional CMT measures may be required to ensure comparisons are made in similar regions of ciliary muscles. Fifth, a recent study observed alternations in CMT after administering 1% atropine [ 59 ]. However, considering the varying accommodative demands between the low and high myopic groups when fixating on the fixation target during measurements, the current study employed two drops of 1% tropicamide to minimize the potential accommodation fluctuations and mitigate their impact on the comparison of CMT between groups [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%